Effect of long-period ordered stacking on twinning behavior and mechanical properties of Mg-Al-Y alloy during uniaxial hot compression. (10th April 2023) - Yuan, Shuai; Wang, Jinhui; Zhang, Lei; Luan, Shiyu; Jin, Peipeng
Highlights: The strengthening temperature range of LPSO in Mg-Al-Y alloy was explored. The effect of LPSO on twinning behavior was investigated in detail. The elevated temperature deformation behavior and microstructure evolution of Mg-Al-Y alloy were studied. Abstract: Two alloys with (T4-4h) and without (T4-8h) long-period stacking ordered (LPSO) phase were obtained by solution treatment of as-cast Mg-1Al-12Y alloy at 540 °C for 4 h and 8 h, respectively. The compressive tests (300–450 °C, ε =0.01s −1 ) showed that the strengthening effect of LPSO in T4-4h alloy gradually disappeared with temperature increase. In addition, the corresponding compression deformation behavior of the two alloys was also investigated by electron backscatter diffraction (EBSD). It was found that the twinning of the two alloys was dominated by 10 1 ¯ 2 extension twins, and the large amount of lamellar LPSO in T4-4 h alloy inhibited the activation and growth of twins. The [0001] // compression direction (CD) texture formed after deformation is mostly attributed to the activation and growth of extension twins. By analyzing the activated twin variants, it was found that the activation of twin variants mainly depended on Schmid factor (SF). For twin variants with smaller SF, they may be activated due to local stress concentration. Based on the analysis results of in-grain misorientation axis (IGMA) and SF, the deformation mechanism of the alloys at elevated temperature is dominated by basal slip and non-basal slip. The stronger mechanical properties of T4-4h alloy than those of T4-8h are attributed to the obstruction of non-basal slip movement by LPSO.